2021
DOI: 10.3389/fcell.2021.681529
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA TMEM220-AS1 Suppressed Hepatocellular Carcinoma by Regulating the miR-484/MAGI1 Axis as a Competing Endogenous RNA

Abstract: Long non-coding RNAs (lncRNAs) have a considerable regulatory influence on multiple biological processes. Nevertheless, the role of TMEM220-AS1 in hepatocellular carcinoma (HCC) remains unclear. We used The Cancer Genome Atlas (TCGA) database to analyze the differentially expressed lncRNAs. qRT-PCR was used to verify the results for a large population. The in vitro effects of TMEM220-AS1 on HCC cells were determined using Cell Counting Kit-8 (CCK-8), 5-ethynyl-2’-deoxyuridine (EdU), flow cytometry, and Transwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The physiological functions of miR-484 in mammals are multifaceted and involve endoplasmic reticulum stress, oxidative stress, inflammation, cell proliferation and apoptosis. Besides, several reports have confirmed the abnormal expression of miR-484 in both tissue and serum specimens from clinical patients (29,30,32). The modalities and regulatory mechanisms of miR-484 regulation of downstream target genes in different types of cells and their microenvironments are unique.…”
Section: Important Characteristics Of Mir-484mentioning
confidence: 96%
See 1 more Smart Citation
“…The physiological functions of miR-484 in mammals are multifaceted and involve endoplasmic reticulum stress, oxidative stress, inflammation, cell proliferation and apoptosis. Besides, several reports have confirmed the abnormal expression of miR-484 in both tissue and serum specimens from clinical patients (29,30,32). The modalities and regulatory mechanisms of miR-484 regulation of downstream target genes in different types of cells and their microenvironments are unique.…”
Section: Important Characteristics Of Mir-484mentioning
confidence: 96%
“…Consistency with the former, hypermethylation at the CpG island site of the miR-484 promoter in microsatellite instability colorectal cancer significantly downregulates miR-484 production ( 33 ). In apart from the above mechanisms, mature miRNAs compete with long-stranded non-coding RNAs (lncRNAs) to bind the 3’-UTR of target mRNAs and indirectly inhibit the negative regulation of target genes by miRNAs, such as lncRNA Ttc3-209 in human retinal cells ( 24 ), PGM5-AS1 in colorectal cancer ( 28 ), TMEM220-AS1 in hepatocellular carcinoma cells ( 29 ), THAP9-AS1 in pancreatic ductal adenocarcinoma ( 30 ) and PCED1B-AS1 in Clear Cell Renal Cell Carcinoma ( 27 ), which are considered as ceRNAs, by competitively inhibiting miR-484 binding and upregulating the translation of target proteins.…”
Section: Important Characteristics Of Mir-484mentioning
confidence: 99%
“…The pathogenesis of HCC is very complicated, involving transcriptional misregulation and cell cycle disorder ( 26 , 27 ), somatic mutation ( 27 ) and abnormal pyroptosis ( 28 ). LncRNAs can affect tumorigenesis and tumor progression in a variety of ways, including regulation of cell proliferation and apoptosis ( 29 ), influencing drug sensitivity ( 30 ), and regulation of cell pyroptosis ( 31 ). Various prognostic prediction models for HCC patients based on lncRNA signatures have been reported ( 22 , 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested that lncRNAs play a key role in the occurrence, development, and metastasis of liver cancer, and they have shown strong survival prediction potential as novel biomarkers ( Hong et al, 2020 ; Li et al, 2020 ; Wan et al, 2021 ; Zhou et al, 2021 ). For example, Cao reported that lncRNA TMEM220-AS1 could suppress HCC cell proliferation and metastasis by regulating the miR-484/MAGI1 axis ( Cao et al, 2021 ). However, the prognostic value and mechanism of pyroptosis-related lncRNAs in HCC have not yet been elucidated and remain to be studied.…”
Section: Discussionmentioning
confidence: 99%